2015
DOI: 10.1002/jsfa.7187
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a d‐psicose 3‐epimerase from Treponema primitiaZAS‐1 and its application on enzymatic production of d‐psicose

Abstract: A novel DPEase from T. primitia ZAS-1 was characterized that could catalyze the formation of D-psicose from D-fructose. D-Psicose was produced at a yield of 137.5 g L(-1) from 500 g L(-1) D-fructose, suggesting that Trpr-DPEase might be appropriate for the industrial production of D-psicose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Importantly, the XI and DPEase enzymes immobilized on yeast spores could be easily harvested and reused for five cycle times without significant loss of activity. However, the yield was still low for D-psicose production in large scale compared with that of one-step reaction catalyzed by DPEase free enzyme using d-fructose as the substrate [21,38,39]. In contrast, Sun and coworkers developed a one-step process for d-psicose production from d-glucose via co-expression of XI and DPEase in E. coli with a conversion yield of 16 % under optimal conditions [19].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Importantly, the XI and DPEase enzymes immobilized on yeast spores could be easily harvested and reused for five cycle times without significant loss of activity. However, the yield was still low for D-psicose production in large scale compared with that of one-step reaction catalyzed by DPEase free enzyme using d-fructose as the substrate [21,38,39]. In contrast, Sun and coworkers developed a one-step process for d-psicose production from d-glucose via co-expression of XI and DPEase in E. coli with a conversion yield of 16 % under optimal conditions [19].…”
Section: Discussionmentioning
confidence: 88%
“…ST-24, Agrobacterium tumefaciens, Rhodobacter sphaeroides SK011, Clostridium cellulolyticum H10, Clostridium scindens 35704, Clostridium bolteae, Treponema primitia ZAS-1, Ruminococcus sp., Mesorhizobium loti, Desmospora sp, and Clostridium sp. have been characterized and employed for d-psicose synthesis [9,11,12,20,21,32,33,[36][37][38][39][40]. DTEases from A. tumefaciens, C. cellulolyticum H10, C. scindens 35704, C. bolteae, T. primitia, Ruminococcus sp., Desmospora sp, and Clostridium sp.…”
Section: Introductionmentioning
confidence: 99%
“…BNL1100 (Mu et al 2013), Clostridium bolteae (Jia et al 2014), Dorea sp. CAG317 , and Treponema primitia (Zhang et al 2016). Finally, a ketose 3-epimerase with the optimum substrate of L-ribulose, named L-ribulose 3-epimerase (EC 5.1.3.31), was first identified from Mesorhizobium loti (Uechi et al 2013b).…”
Section: C-3 Epimerization Between L-ketohexosesmentioning
confidence: 97%
“…DPEase, T. primitia DPEase and Dorea sp. DPEase (Zhang et al, 2016;Zhang, Fang, Zhang, et al, 2013;Zhang et al, 2015). In addition, the thermostability might be increased through molecular modification.…”
Section: Temperaturementioning
confidence: 98%
“…Among all ketose 3-epimerases reported, DPEase from Treponema primitia as well as DPEase from Dorea sp., exhibited the highest optimum temperature of 70 C (Zhang, Zhang, Jiang, & Mu, 2016;Zhang et al, 2015), while DTEase from Rhodobacter sphaeroides showed the lowest optimum temperature of 40 C (Zhang et al, 2009). It is generally known that an elevated operating temperature is required for the industrial production of rare sugars, because high reaction temperatures could induce higher reactivity (a higher reaction rate and lower diffusional restrictions), lower viscosity, higher stability, higher process yield (increased solubility of substrates and products and a favorable equilibrium displacement during endothermic reactions), and less contamination (Mozhaev, 1993).…”
Section: Temperaturementioning
confidence: 99%